The Continued Operation of the Nuclear Deterrence: United States of America and The Russian Federation - Fuentes, Carolina (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The proliferation of nuclear weapons has been, and continues to be, a debate among academics, military strategists, and statists. President Vladimir Putin's order to put Russia's nuclear deterrent forces on high alert has raised fears of a possible "nuclear war" amid the conflict between Russia and Ukraine. Through a descriptive historical method of the operation of nuclear weapons during the Cold War, this article has as its main objective, the outline of a forecast on the nuclear risk, in the current crisis between Russia and Ukraine.